ANALISIS WAYANG GOLEK BOGOR DAN WAYANG POTEHI JOMBANG DALAM STRUKTUR BAHAN PEMBUATAN DAN ALUR PEMENTASAN - Leonardo, Ong Peter; Widiartha, Lidwina Jacinda (Seminar Nasional Ilmu Terapan, 2024)
The continuous popularity of wayang up to the present day demonstrates its importance and significance in people's lives. Wayang Golek and Wayang Potehi are two forms of wayang that have their own unique characteristics. Wayang Potehi, of Chinese descent, uses puppets and often depicts stories about Chinese figures and legends. Developed from wayang kulit, wayang golek is made of wood and tells the stories of the Ramayana and Mahabharata, the cultural heritage of Java. Both types of wayang have similarities in terms of history and both use wood as the main material for making puppets. This research focuses on the comparison and similarities between Wayang Potehi from Jombang and Wayang Golek from Bogor, specifically in terms of materials and tools used in production, as well as the performance flow. The aim is to determine whether there is a strong connection between the two types of wayang and to understand how their histories are related. The research questions include the materials used in the making of wayang and the performance flow of both types of wayang.